2021
DOI: 10.2116/analsci.20scr12
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors as Evolvable Biosensors

Abstract: One of the most prominent features of genetically encoded biosensors (GEBs) is their evolvability-the ability to invent new sensory functions using mutations. Among the GEBs, the transcription factor-based biosensors (TF-biosensors) will be the focus of this review. We will also discuss how this class of sensors can be highly evolvable and how we can exploit it. With an established platform for directed evolution, researchers can create, or evolve, new TF-biosensors. Directed evolution experiments have reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…An evolutionary platform for genetic switches in yeast was recently demonstrated [18,45,66] and thus, the number of such synthetic switches has rapidly increased, highlighting the potential of prokaryotic TFs as an untapped resource for yeast genetic switches. Umeno et al argued that TFs are intrinsically evolvable; therefore, mutants that are responsive to non-native compounds can be attained within a few directed evolution cycles [37]. Indeed, dozens of new or evolved genetic switches (biosensors) based on bacterial TFs have been reported within the last 3 years [1,[105][106][107][108][109][110][111][112][113].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An evolutionary platform for genetic switches in yeast was recently demonstrated [18,45,66] and thus, the number of such synthetic switches has rapidly increased, highlighting the potential of prokaryotic TFs as an untapped resource for yeast genetic switches. Umeno et al argued that TFs are intrinsically evolvable; therefore, mutants that are responsive to non-native compounds can be attained within a few directed evolution cycles [37]. Indeed, dozens of new or evolved genetic switches (biosensors) based on bacterial TFs have been reported within the last 3 years [1,[105][106][107][108][109][110][111][112][113].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial transcription repressors can reverse their switching behavior by introducing mutations to them [37]. Thus, opposite regulation can be achieved by using mutant sTAs with these reversed mutations (Figure 1B).…”
Section: Stas Based On Bacterial Transcriptional Co-repressors and Ac...mentioning
confidence: 99%
“…Because the evolutionary platform for genetic switches in yeast has recently been demonstrated (15,45,55), the number of such synthetic switches has rapidly increased, which highlights the potential of prokaryotic TFs as an untapped resource for yeast genetic switches. Besides, Umeno et al argued that TFs are intrinsically evolvable; therefore, mutants that are responsive to non-native compounds can be reached within a few directed evolution cycles (89). Indeed, dozens of new or evolved genetic switches (biosensors) based on bacterial TFs have been reported within the last 2 years (1,90,91,92,93,94,95,96,97,98).…”
Section: Discussionmentioning
confidence: 99%
“…An example can be found in the work of Rottinghaus and others, where new variants were engineered from promiscuous amino acid-specific TFs to specifically detect similar amino acids and neurotransmitters ( Rottinghaus et al, 2022 ). A review on the evolvability of TF-based biosensors can be found in ( Umeno et al, 2021 ). This may produce several hundreds of variants, and most of them may show equal or poorer performance, which requires a faster and simpler approach that quickly identifies and isolates good performers and discards variants that do not meet the designer’s criteria.…”
Section: Biosensor Designmentioning
confidence: 99%